Characterization of Microsatellite Loci in the Western Subterranean Termite, Reticulitermes hesperus, and Cross-Amplification in Closely Related Cryptic Species - Copren, Kirsten A. (University of Wisconsin Library, 2007)
New, and previously reported microsatellites, were characterized for a group of four cryptic sibling species in California (USA) in the subterranean termite genus Reticulitermes with the goal of finding loci appropriate for population and species level studies. Three new microsatellites were identified originating from R. hesperus, and 19 loci previously characterized in R. flavipes and R. santonensis were examined. Of the three loci specifically developed for R. hesperus, none amplify with the other species. Variation appropriate for population level studies was found in 4–13 loci depending on the species. Fifteen loci appeared to be appropriate for use at the species level. Unique or monomorphic alleles are found among the four species, indicating these loci will be taxonomically informative for this group.